2017
DOI: 10.18632/oncotarget.15370
|View full text |Cite
|
Sign up to set email alerts
|

Tissue transglutaminase induces Epithelial-Mesenchymal-Transition and the acquisition of stem cell like characteristics in colorectal cancer cells

Abstract: Human colon cancer cell lines (CRCs) RKO, SW480 and SW620 were investigated for TG2 involvement in tumour advancement and aggression. TG2 expression correlated with tumour advancement and expression of markers of epithelial-mesenchymal transition (EMT). The metastatic cell line SW620 showed high TG2 expression compared to the primary tumour cell lines SW480 and RKO and could form tumour spheroids under non- adherent conditions. TG2 manipulation in the CRCs by shRNA or TG2 transduction confirmed the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 55 publications
7
43
0
Order By: Relevance
“…The role of TGF β in EMT 12 , 13 and EndMT 14 has been well-documented. Given the comparable effects of either exogenous TG2 or TGF β 1 that result in the loss of HUVEC tubule formation, we next looked at the effects of TG2 on TGF β 1 signalling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of TGF β in EMT 12 , 13 and EndMT 14 has been well-documented. Given the comparable effects of either exogenous TG2 or TGF β 1 that result in the loss of HUVEC tubule formation, we next looked at the effects of TG2 on TGF β 1 signalling.…”
Section: Resultsmentioning
confidence: 99%
“…If progressive, EndMT will eventually lead to the loss of blood vessel formation (capillary rarefaction) and ultimately organ fibrosis and failure. Importantly, TG2 has also been shown to be involved in a similar process called epithelial–mesenchymal transition (EMT) important during cancer progression 13 and in cystic fibrosis, 12 It is therefore not surprising that TG2 is also involved in EndMT.…”
Section: Discussionmentioning
confidence: 99%
“…For several tissue-derived cells of heterogeneous origin, grown in an appropriate microenvironment, the spheroid (niche-like)-forming capacity per se is typical of stem/progenitor cells, irrespectively of their normal or neoplastic nature [ 1 , 64 , 104 , 105 ]. This spheroid self-building property can be considered as an EMT-dependent process, mediated by TGF-β and its network signaling.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…More importantly, the activation of the EMT process is closely related to the normal and maintenance of the dryness of the tumor cells. A large number of experimental studies have confirmed that EMT can induce the transformation of tumor cells into cancer stem cells [ 80 , 81 ]. Overexpression of EMT-associated transcription factors Snail, Twist, or FOXC2 not only enables phenotypic transformation of breast cancer cells but also enhances tumor glomus formation, soft agar clonality, and tumorigenic potential and enables them to obtain CD44high/CD24low (cancerous CSCs and markers for mammary epithelial stem cells) antigen phenotype [ 82 , 83 ].…”
Section: Cancer Stem Cells and Plasticitymentioning
confidence: 99%